Recombination between Fusarium oxysporum telomeres and pUC ampicillin resistance gene in a transforming vector. - W. A. Powell; Z. H. Yan (Fungal Genetics Reports, 1995)
Transformations using certain vector/host combinations of Fusarium oxysporum have been shown to promote in vivo production of linear, autonomously replicating plasmids (Powell and Kistler, 1990, J. Bact. 172:3163-3171). The modifications to the transforming vector included: linearization of a circular plasmid, addition of putative fungal telomeres to one end of the plasmid, and duplication and translocation of the modified DNA to the other end of the plasmid. This report confirms that the putative telomere repeats (TTAGGG) from one of these fungal-modified vectors, pFOLT4R4, are also located at the ends of F. oxysporum chromosomes and indicates that these telomere sequences were added to the vector by a recombinational event.